Mongolčuudtaj cug horiotoj Lhas ruu ajalsan nʹ Castyn orond tohioldson adal javdal - Hedin, Sven Anders 1865-1952 (Mönhijn Üsėg, 2014)
Travel Notes about late 19th century Mongolia and Tibet
Keywords: Travel; Reisebericht; Tibet Autonomous Region (China) / Description and travel; Mongolia / Description and travel; China / Tibet Autonomous Region; Mongolia; China; Mongolei; Tibet